Impact of free provision of disinfectant wipes combined with bundle management on the prevention of multi-drug resistant organism infections in the respiratory and intensive care unit - Yu-Dan Wang; Jian-Hong Liang; Xie-Nan Gao; Li-Li Ma; Shen-Shen Huang; Yong-Mei Zhang (Frontiers in Cellular and Infection Microbiology)
ObjectiveTo explore the role of free provision of disinfectant wipes combined with bundle management in preventing Multi-Drug Resistant Organism (MDRO) infections in the Respiratory and Intensive Care Unit (RICU).MethodsThis study included patients admitted to the RICU between January 2022 and June 2023 (control group) and from July 2023 to June 2024 (intervention group), all of whom met the inclusion criteria. The control group received standard bundle management measures, while the intervention group received unlimited use of disinfectant wipes combined with bundle management. The MDRO discovery rates and hospital-acquired infection incidence rates were compared between the two groups to assess the impact of free disinfectant wipe provision on MDRO infection prevention in the RICU.ResultsThere were no significant differences between the two groups in terms of patient age and baseline characteristics, except for Sex and the proportion of patients with chronic respiratory diseases. Notably, the MDRO discovery rate, MDRO infection rate, and hospital-acquired infection incidence were all significantly lower in the intervention group compared to the control group (MDRO discovery rate: 35.2% vs 45.9%, P<0.001; MDRO infection rate: 0.8% vs 3.5%, P = 0.003; hospital-acquired infection rate: 1.5% vs 3.52%, P=0.030). However, the intervention group had more percentage of patients receiving mechanical ventilation and longer ICU stay (P < 0.05). Furthermore, in-hospital mortality was lower in the intervention group (19.5% vs 13.5%, P < 0.05).ConclusionThe combined intervention of unlimited use of disinfectant wipes with bundle management significantly reduced MDRO hospital-acquired infection rates and in-hospital mortality in the RICU, demonstrating its effectiveness in infection prevention.